Campur Kode dalam Tuturan Mahasiswa Gayo Di Banda Aceh - Ida Gustina; Rostina Taib; Muhammad Iqbal (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
This research aims to determine the forms of code mixing in Gayonese speech by Gayonese students in Banda Aceh. The data source of this study was the Gayonese students. The method used is a qualitative descriptive method. The data source of this research is native speakers of the Gayonese language who live in the Banda Aceh region. The data collection technique used was a technique, speaking freely and speaking on the basis of listening and tapping then followed by recording and taking notes. The results of this study indicate that the mixed code forms used by Gayonese students are word form, phrase form, baster form, word repetition form, idiom or expression form, and clause form. Thus, it can be concluded that all forms of code mixing are found in the speech of Gayonese students